Analysis of Student and Teacher Social and Gender Relations: A Sociological Perspective - Nelson Hasibuan; Ruth Judica Siahaan; Mario Alberto Manodohon (HK-Publishing, 2022)
AbstractThis study aims to describe how social and gender relations are in the learning process in the classroom as well as activities and social interactions between students and teachers of sociology subjects as well as with the whole community of High School. The research result verifiers indicate the selection High School tight enough to make the background as diverse as the students do not have close family and financially capabilities. Social class does not affect the learning process and facility use. There is positive competition among students such as achievement competition, student council elections, and the election of the chair of other organizations in the school environment.Keywords: gender relations, social relations, hidden curriculum. AbstractPenelitian ini bertujuan untuk mendeskripsikan bagaimana relasi sosial dan gender dalam proses pembelajaran di kelas serta aktivitas dan interaksi sosial antara siswa dan guru mata pelajaran sosiologi serta dengan seluruh masyarakat SMA. Verifikator hasil penelitian menunjukkan bahwa seleksi SMA cukup ketat dengan latar belakang yang beragam karena siswa tidak memiliki keluarga dekat dan kemampuan finansial. Kelas sosial tidak mempengaruhi proses belajar dan penggunaan fasilitas. Adanya persaingan positif antar siswa seperti persaingan prestasi, pemilihan OSIS, dan pemilihan ketua organisasi lain di lingkungan sekolah.Kata kunci: hubungan gender, hubungan sosial, kurikulum tersembunyi.